Pemberdayaan Masyarakat dalam Meningkatkan Ketahanan Keluarga Melalui Program Kampung Bebas Rentenir : Studi Kasus Kelompok Bina RPM di Parakan - Salsabila Zahra; Almisar Hamid (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This research discusses community empowerment in social conditions where problems occur in the community, especiallymothers or lower middle class people who are looking for a shortcut to finance familylife on basicneeds by lending money from moneylenders. That the familyis high, the low average familyincome and the high cost of living make them feel that their quality of life is threatened. The solution to overcome this problem must be a driving agency from the government or what is meant is community empowerment, namely the Leder-Free Village (KBR) Program which provides spiritual training, training assistance, business capital to the community so that prosperous and quality families are created. This research aims to determine the process of stages of community empowerment activities,family resilience and determine the supporting and inhibiting factors in the Money Loan Free Village program. This research uses a descriptive qualitative approach. Data collection techniques using interview, observation and documentation techniques. The results of this research show that the Leder-Free Village program achieves community empowerment in terms of family resilience, namely that the beneficiary members get business capital and create social change from economic, social and spiritual independence, so that achieve the condition of the family in their lives independently and more empowered.